2012
DOI: 10.1080/10934529.2012.640243
|View full text |Cite
|
Sign up to set email alerts
|

QSAR and ANN for the estimation of water solubility of 209 polychlorinatedtrans-azobenzenes

Abstract: Polychlorinated trans-azobenzenes (PCt-ABs) are less studied a highly toxic impurity in 2,3-dichloroaniline (2,3-D) and some herbicides and are compounds of environmental relevance lacking experimental physical and chemical properties data. In this study, to fulfill gaps on environmentally relevant partitioning properties of PCABs, the values of water solubility (μg/L and log S) have been determined for 209 congeners of chloro-trans-azobenzene (Ct-AB) by means of quantitative structure - property relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Log P values of 3.82 [17] and 4.11 [20] have been reported for 1 and log P = 3.4 for dipeptide 8 [17]. Using the method of Abraham [21] we obtained S w (trans) values of 0.07 and 0.03 mM for AB 1, similar to our results in Table 1 (Table S1). The t R values for the trans isomers fell within a small range, as did values for cis isomers; t R (trans) = 40 ± 4 and t R (cis) = 30.0 ± 4 min.…”
Section: Scheme 1 Compounds Used In This Studysupporting
confidence: 86%
See 2 more Smart Citations
“…Log P values of 3.82 [17] and 4.11 [20] have been reported for 1 and log P = 3.4 for dipeptide 8 [17]. Using the method of Abraham [21] we obtained S w (trans) values of 0.07 and 0.03 mM for AB 1, similar to our results in Table 1 (Table S1). The t R values for the trans isomers fell within a small range, as did values for cis isomers; t R (trans) = 40 ± 4 and t R (cis) = 30.0 ± 4 min.…”
Section: Scheme 1 Compounds Used In This Studysupporting
confidence: 86%
“…Given the number of literature reports on AB-peptide conjugates, it is important to fully understand model systems like 8-10. Chambers and Haworth [21] observed ~30% cis for NMR samples of 8 and 10 in buffered D 2 O; the authors postulated intramolecular stabilization of the cis isomer. Our results do not support this hypothesis; instead we propose a solubility-driven isomerization.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that solubility was strongly affected by three variables: energy of the lowest unoccupied molecular orbital, most positive atomic partial charge in the molecule, and the quadrupole moment. The water solubility of 209 congeners of chloro-trans-azobenzene was modeled using Genetic Algorithm-Artificial Neural Network (GA-ANN) (Wilczyńska-Piliszek et al, 2012). Non-ionic perfluorinated chemicals were studied using two-dimensional descriptors (Bhhatarai and Gramatica, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…GA-ANN has been applied in different studies [175][176][177][178][179][180][181][182][183]. Application of the specific combined versions of ANN with GA can be found in QSAR/QSPR studies.…”
mentioning
confidence: 99%